Poly(ADP-ribose) polymerase gene disruption conferred mice resistant to streptozotocin-induced diabetes - Masutani, Mitsuko (The National Academy of Sciences, 1999)
Streptozotocin (STZ), a glucose analogue known to induce diabetes in experimental animals, causes DNA strand breaks and subsequent activation of poly(ADPribose) polymerase (Parp). Because Parp uses NAD as a substrate, extensive DNA damage will result in reduction of cellular NAD level. In fact, STZ induces NAD depletion and cell death in isolated pancreatic islets in vitro. Activation of Parp therefore is thought to play an important role in STZ-induced diabetes. In the present study, we established Parp-deficient (Parp(−/−)) mice by disrupting Parp exon 1 by using the homologous recombination technique. These mice were used to examine the possible involvement of Parp in STZ-induced β-cell damage in vivo. The wild-type (Parp(+/+)) mice showed significant increases in blood glucose concentration from 129 mg/dl to 218, 370, 477, and 452 mg/dl on experimental days 1, 7, 21, and 60, respectively, after a single injection of 180 mg STZ/kg body weight. In contrast, the concentration of blood glucose in Parp(−/−) mice remained normal up to day 7, slightly increased on day 21, but returned to normal levels on day 60. STZ injection caused extensive necrosis in the islets of Parp(+/+) mice on day 1, with subsequent progressive islet atrophy and loss of functional β cells from day 7. In contrast, the extent of islet β-cell death and dysfunction was markedly less in Parp(−/−) mice. Our findings clearly implicate Parp activation in islet β-cell damage and glucose intolerance induced by STZ in vivo.